The Features of the Production, Financial-Accounting and Human Resources Functions in the SMEs - Eugen BURDUŞ; Ioan URSACHI; Florica BADEA (Revista de Management Comparat International, 2009)
Managers of any organization exercising the functions of management, organization, coordination, training and control in different areas, which generally are called functions of the organization.